FABLE AND VISUAL POETRY: AN APPROXIMATION BY THE THEORY OF GENRES - Buoro, Thiago [UNESP] (Univ Estadual Mato Grosso Sul, 2019)
The fable and the visual poem are discussed here. The convergence between these two apparently distinct forms of discourse is observed in the fact that they share a certain generic imprecision. Although they have long been recognized as autonomous discourses, fables and visual poetry are not easily included in the typology of literary genres, for reasons that will be investigated by way of comparison, which has the benefit of pointing out the generality of the problem and justifying it under less closed outlooks.
Keywords: fable; visual poetry; literary genre